Streamlining Sales Operations with Salesforce Flow Builder: A Technical Guide - Sritulasi Shreedharan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines Salesforce Flow Builder’s transformative impact on enterprise sales operations and process automation. The article investigates how Flow Builder revolutionizes traditional sales processes by reducing manual intervention, enhancing data accuracy, and streamlining operational workflows. Through extensive analysis of implementations across global organizations, the article demonstrates Flow Builder’s effectiveness in optimizing sales cycles, improving team productivity, and ensuring consistent process execution. The article highlights significant improvements in areas including automation development, system reliability, data integration, and user adoption rates, establishing Flow Builder as a cornerstone technology for modern enterprise automation.